ZDHHC11-mediated AXL palmitoylation promotes osimertinib resistance in non-small-cell lung cancer - He Cui; Xueting Cai; Qiang Qian; Shuyuan Fan; Tian Li; Ting Wang; Haixuan Dai; Yunwei Song; Xiaoyan Sun; Peng Cao (Proceedings of the National Academy of Sciences, 2025)
Receptor tyrosine kinase pathway rewiring represents a fundamental mechanism underlying acquired resistance to EGFR tyrosine kinase inhibitors in EGFR-mutant non-small-cell lung cancer (NSCLC). While posttranslational modifications facilitate aberrant activation of bypass signaling networks, the specific contribution of ZDHHC palmitoyl acyltransferase-mediated palmitoylation remains poorly characterized. Here, ZDHHC11-mediated palmitoylation contributes to osimertinib resistance in EGFR-mutant NSCLC. Patient samples, along with in vitro and in vivo functional studies, indicated that ZDHHC11 upregulation reduces the sensitivity of tumor cells to osimertinib by promoting malignant phenotype. Mechanistically, we establish AXL receptor tyrosine kinase as the critical substrate. ZDHHC11 catalyzes AXL palmitoylation at Cys869, inducing plasma membrane retention and constitutive activation. This triggers downstream PI3K–AKT signaling, with AXL knockout alleviating the effect of ZDHHC11-driven resistance. Crucially, pharmacological inhibition ZDHHC11-mediated palmitoylation with the broad-spectrum palmitoylation inhibitor 2-bromopalmitate effectively augmented the antitumor effects of osimertinib. Collectively, ZDHHC11 regulates osimertinib resistance in a palmitoylation-dependent manner. Targeting the ZDHHC11–AXL axis may provide a promising therapeutic strategy for the treatment of osimertinib-resistant EGFR-mutant NSCLC patients with high ZDHHC11 expression.